2001
DOI: 10.1590/s0103-84782001000500016
|View full text |Cite
|
Sign up to set email alerts
|

Predatory activity of Arthrobotrys oligospora and Duddingtonia flagrans on pre-parasitic larval stages of cyathostominae under different constant temperatures

Abstract: SUMMARYThe effect of different temperatures on the predatory activity of Arthrobotrys oligospora and Duddingtonia flagrans on the free-living larval stages of cyathostomes were evaluated in an experiment where feces of horses containing the parasites' eggs were treated with these fungi and incubated under different constant temperatures (10°C, 15°C, 20°C, 25°C and 30°C

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
0
7
0
2
Order By: Relevance
“…Such fact prevented a satisfactory evaluation of the predatory activity of the fungus from December 2007 to February 2008, when an evident increase in larval reduction percentage in the pasture was observed. The temperature averages were satisfactory for fungal activity during the whole study, according to Santos et al (2001). In their study regarding the predatory activity of D. flagrans on infective cyathostomine larvae at different temperatures, the fungus showed better reduction percentages at 25-30°C.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Such fact prevented a satisfactory evaluation of the predatory activity of the fungus from December 2007 to February 2008, when an evident increase in larval reduction percentage in the pasture was observed. The temperature averages were satisfactory for fungal activity during the whole study, according to Santos et al (2001). In their study regarding the predatory activity of D. flagrans on infective cyathostomine larvae at different temperatures, the fungus showed better reduction percentages at 25-30°C.…”
Section: Resultsmentioning
confidence: 94%
“…The predatory activity of D. flagrans upon equine nematodes was already studied in vitro, showing more than 80% efficacy in reducing the number of infective Strongylidae larvae (Bird and Herd 1995;Fernandez et al 1997;Fernandez et al 1999;Santos et al 2001). Fernandez et al (1997Fernandez et al ( , 1999 and Baudena et al (2000) also evaluated the activity of D. flagrans in the biological control of equine Strongylidae.…”
Section: Introductionmentioning
confidence: 99%
“…Em temperaturas inferiores, a taxa de crescimento é mais lenta, ao passo que, em temperaturas superiores, o fungo não cresce (Santos, 2000). Em estudo realizado por Santos et al (2001), foi observado que entre 25 e 30°C D. flagrans reduziu acima de 90% de L 3 de ciatostomíneos. Os mesmos autores constataram que 25°C foi a temperatura que proporcionou o maior índice de desenvolvimento de ovos até L 3 desses parasitos.…”
Section: Resultsunclassified
“…Fernández et al (1999) reported that D. flagrans reduced the number of Cooperia oncophora larvae by 70-96% at 15°C and 63-98% at 20°C. Santos et al (2001) reported that D. flagrans caused 90% reduction in the number of cyathostomes L3 larvae at 25 and 30°C. According to Buske et al (2013), the best temperature for the nematicidal action of D. flagrans was 30°C, in which the fungus was responsible for a 74.5% reduction of the L3 of Haemonchus contortus.…”
Section: Discussionmentioning
confidence: 99%